Synthesis and structure of two-dimensional transition-metal dichalcogenides - Shi, Yumeng (2018)
Two-dimensional (2D) transition-metal dichalcogenides (TMDCs) exhibit unique electrical, optical, thermal, and mechanical properties, which enable them to be used as building blocks in compact and lightweight integrated electronic systems. The controllable and reliable synthesis of atomically thin TMDCs is essential for their practical application. Recent progress in large-area synthesis of monolayer TMDCs paves the way for practical production of various 2D TMDC layers. The intrinsic optical and electrical properties of monolayer TMDCs can be defined by stoichiometry during synthesis. By manipulating the lattice structure or layer stacking manner, it is possible to create atomically thin van der Waals materials with unique and unexplored physical properties. In this article, we review recent developments in the synthesis of TMDC monolayers, alloys, and heterostructures, which shine light on the design of novel TMDCs with desired functional properties.